Modeling and Simulation of the Vibration Characteristics of the In-Wheel Motor Driving Vehicle Based on Bond Graph - Di Tan; Qiang Wang (Shock and Vibration)
Bond graph theory is applied to the modeling and analysis of the vibration characteristics of the in-wheel motor driving vehicle. First, an 11-degree-of-freedom vibration model of the in-wheel motor driving vehicle is established based on bond graph, and then the correctness of the model is verified. Second, under the driving condition of class B road excitations and a speed of 50 Km/h, the vibration characteristics of the in-wheel motor driving vehicle are simulated and analyzed, and the activity of each part in the system is then calculated. Third, these parts that have less of an effect on the vibration characteristics of an in-wheel motor driving vehicle are identified according to the magnitude of the activity, and then the model is simplified by removing these parts. Finally, the reliability of the simplified model is verified by comparing the vibration characteristics of the model before and after simplification. This study can provide a method for the modeling and simulation of the vibration characteristics of the in-wheel motor driving vehicle.